Diversity of Trichoderma species associated with the black rot disease of Gastrodia elata, including four new species - Ye, Chuwen; You, Yanbo; Li, Wenjie; Jing, Tingting; Mo, Minghe; Qiao, Min; Yu, Zefen (Frontiers in Microbiology, 2024)
Trichoderma, as an environmental opportunist, exhibits adaptability to diverse habitats.Trichoderma engages in symbiotic relationships with plants through both parasitic and mutualistic mechanisms. While some of Trichoderma act as plant pathogenic fungi, others employ various strategies to protect and enhance plant growth. This study reports 13 Trichoderma species isolated from diseased tubers of Gastrodia elate in Yunnan, China, including nine known species and four new species, T. delicatum, T. robustum, T. perfasciculatum, and T. subulatum. Among known species, T. hamatum has the highest frequence. The phylogenetic positions of four new species were determined through the multi-gene analysis relying on the internal transcribed spacer regions of the ribosomal DNA (ITS), the translation elongation factor 1-α encoding gene (tef1-α), and the gene encoding the second largest nuclear RNA polymerase subunit (rpb2). T. delicatum belongs to the Koningii clade, while T. robustum and T. perfasciculatum are assigned to the Virens clade, and T. subulatum emerge as a new member of the Spirale clade. This study provides the morphological features of new species, and discussed morphological differences from those of phylogenetically close species. The findings establish a foundation for research aiming at preventing and managing diseases affecting G. elate.